Methodological proposal for validation of the disinfecting efficacy of an automated flexible endoscope reprocessor - Kazuko Uchikawa Graziano; Marta Elisa Auler Pereira; Elaine Koda (Revista Latino-Americana de Enfermagem)
ABSTRACT Objective: to elaborate and apply a method to assess the efficacy of automated flexible endoscope reprocessors at a time when there is not an official method or trained laboratories to comply with the requirements described in specific standards for this type of health product in Brazil. Method: the present methodological study was developed based on the following theoretical references: International Organization for Standardization (ISO) standard ISO 15883-4/2008 and Brazilian Health Surveillance Agency (Agência Nacional de Vigilância Sanitária - ANVISA) Collegiate Board Resolution (Resolução de Diretoria Colegiada - RDC) no. 35/2010 and 15/2012. The proposed method was applied to a commercially available device using a high-level 0.2% peracetic acid-based disinfectant. Results: the proposed method of assessment was found to be robust when the recommendations made in the relevant legislation were incorporated with some adjustments to ensure their feasibility. Application of the proposed method provided evidence of the efficacy of the tested equipment for the high-level disinfection of endoscopes. Conclusion: the proposed method may serve as a reference for the assessment of flexible endoscope reprocessors, thereby providing solid ground for the purchase of this category of health products.